Stamina Prediction of Cows and Goats to Exercise Changes by Measuring Body Temperature, Heart Rate, and Respiratory Rate - Kusmandari Indah Prahesti; Sudirman Baco; Ratmawati Malaka (Hasanuddin Journal of Animal Science (HAJAS), 2021)
Environmental factors play an important role in livestock life. An unsuitable environment can cause disturbances to the growth of animal and cannot produce properly. The purpose of this study was to determine changes in respiratory frequency, heart rate and body temperature of cows and goats at rest, when given running training, and when a rest one hour after being rushed, to find out the stamina of the animals. The results showed that exercise treatment had a very significant effect on respiratory rate, body temperature, and heart rate. The respiratory rate after exercise was significantly different from the respiratory frequency before exercise and after resting for one hour, but quickly returned to normal after one hour rest which indicates that the stamina of these two animals is very good.